Daily field checking list by Walter Rosene, August 12, 1936 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated August 12, 1936. This checklist was used by Walter Rosene to record birds sighted around an island in the Mississippi river near McGregor with a group of people between 5:30 and 8:30. Plustek--flatbed